2009
DOI: 10.1287/isre.1090.0237
|View full text |Cite
|
Sign up to set email alerts
|

Coevolving Systems and the Organization of Agile Software Development

Abstract: Despite the popularity of agile methods in software development and increasing adoption by organizations there is debate about what agility is and how it is achieved. The debate suffers from a lack of understanding of agile concepts and how agile software development is practised. This paper develops a framework for the organization of agile software development that identifies enablers and inhibitors of agility and the emergent capabilities of agile teams. The work is grounded in complex adaptive systems (CAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
205
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(209 citation statements)
references
References 50 publications
3
205
0
1
Order By: Relevance
“…Using thought trials, the taxonomy showed that agility of a method and its underlying components can be tested in a generic sense; practices publicly accepted to be agile might not actually contribute to agility in every instance, and conversely, practices not traditionally recognized for their agility might make a significant contribution. This notion of agile capabilities, also referred to by Vidgen and Wang (2009) in this journal issue, represents a distinct departure from current thinking on ISD agility, where it is often crudely measured by the number of XP or Scrum practices used, regardless of their suitability to the project context or how they are implemented. In addition, the definition and taxonomy both have implications on the conceptual shortcomings of the agile method literature discussed earlier.…”
Section: Definition and Taxonomy Of Isd Agilitymentioning
confidence: 99%
“…Using thought trials, the taxonomy showed that agility of a method and its underlying components can be tested in a generic sense; practices publicly accepted to be agile might not actually contribute to agility in every instance, and conversely, practices not traditionally recognized for their agility might make a significant contribution. This notion of agile capabilities, also referred to by Vidgen and Wang (2009) in this journal issue, represents a distinct departure from current thinking on ISD agility, where it is often crudely measured by the number of XP or Scrum practices used, regardless of their suitability to the project context or how they are implemented. In addition, the definition and taxonomy both have implications on the conceptual shortcomings of the agile method literature discussed earlier.…”
Section: Definition and Taxonomy Of Isd Agilitymentioning
confidence: 99%
“…There is a long tradition of applying systems theory to organisations [28,29]. Also, several authors have used a Complex Adaptive Systems view to explain agile methods in organisational contexts [30][31][32][33]. A system is an interconnected set of elements forming a whole that has properties belonging to the whole.…”
Section: How Do Practitioner Challenges Manifest Themselves In Organimentioning
confidence: 99%
“…They have a long tradition in IT development projects and are currently still broadly used, especially in the manufacturing industry [35,43]. Traditional methods are characterized by a pre-planning stage that is followed by the execution, which makes them less flexible in comparison to agile methods [9,43]. Additionally, unlike agile methods, they have a clear hierarchy within the team [9].…”
Section: Agile and Traditional Project Management Methodsmentioning
confidence: 99%
“…Traditional methods are characterized by a pre-planning stage that is followed by the execution, which makes them less flexible in comparison to agile methods [9,43]. Additionally, unlike agile methods, they have a clear hierarchy within the team [9]. The collaboration is less close than in an agile project team.…”
Section: Agile and Traditional Project Management Methodsmentioning
confidence: 99%
See 1 more Smart Citation